Air pollution and child development in India - Balietti, Anca; Datta, Souvik; Veljanoska, Stefanija (Journal of environmental economics and management, 2022)
In this paper, we study the impact of air pollution on child growth in India. We rely on wind direction to capture quasi-random variation in three main criteria air pollutants. We show that an increase in the average concentration of fine particulate matter by one standard deviation is accountable for almost 5 and 2.4 percentage points of stunting and severe stunting rates, respectively. We also find that ozone and carbon monoxide impact weight-related outcomes. Stunting has critical long-term health and economic consequences; through its impact on stunting, pollution exacerbates the height premium in earnings, with girls being more adversely affected than boys in India.
Gesehen am 27.06.2022